EFEKTIVITAS SLOW STROKE BACK MASSAGE TERHADAP NYERI PERINEUM DERAJAT 2 PADA IBU NIFAS 2 JAM POST PARTUM - Tuti Meihartati; Sumiati .; Chandra Sulistyorini (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Based on the interviews result obtained by mothers who have rupture perineum, the way the treatment is given to reduce pain only by using pharmacological methods and research of slow stroke back massage. Slow stroke back massage is a gentle, slow massage, with a rhythmic emphasis on the thoracic area 10 to 12 and lumbar 1 which is the source of innervations of the uterus and cervix, conducted as much as 60 massage in one minute and done within 5 minutes. This study aims to determine the slow stroke back massage effectiveness against perineum pain on degree 2 to postpartum in 2 hours post partum. The study design was Quasy exprimental with pre and post test without control. The sample in this study were 20 postpartum with rupture perineum on degree 2. The result of this study was wilcoxon test obtained p value <005 (0,002) it means that there was slow stroke back massage effectiveness against perineum pain on degree 2 to postpartum in 2 hours post partum. The conclusion in this study that there was slow stroke back massage effectiveness against perineum pain on degree 2 to postpartum in 2 hours post partum. It is recommended that slow stroke back massage is used as SOP in postpartum midwifery care in particular to reduce perineum pain in postpartum